The Mechanism of Action of the Market of Higher Education Services - Vaxabov A.V., Zaxidova Sh. Sh. (International Journal of Advanced Science and Technology, 2020)
This article discusses the mechanism of the higher education services market and the factors influencing it, models of reforming the higher education system in the world, the interaction with the labor market, sources of funding.